2017
DOI: 10.3389/fneur.2017.00087
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy Mechanisms in Neurocutaneous Disorders: Tuberous Sclerosis Complex, Neurofibromatosis Type 1, and Sturge–Weber Syndrome

Abstract: Neurocutaneous disorders are multisystem diseases affecting skin, brain, and other organs. Epilepsy is very common in the neurocutaneous disorders, affecting up to 90% of patients with tuberous sclerosis complex (TSC) and Sturge–Weber syndrome (SWS), for example. The mechanisms underlying the increased predisposition to brain hyperexcitability differ between disorders, yet some molecular pathways overlap. For instance, the mechanistic target of rapamycin (mTOR) signaling cascade plays a central role in seizure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 149 publications
(180 reference statements)
1
57
1
2
Order By: Relevance
“…Experimental trails and clinical observations confirmed that inhibition of the mTOR pathway is an attractive therapeutic option, and that it may modify the process of epileptogenesis (Curatolo, 2015;Krueger et al, 2013;Sadowski, Kotulska-Jóźwiak, & Jóźwiak, 2015;Samueli et al, 2016;Stafstrom, Staedtke, & Comi, 2017 (French et al, 2016). The reduction of ≥50% in seizure frequency was significantly higher in patients treated…”
Section: Marijuana Derivativesmentioning
confidence: 86%
See 1 more Smart Citation
“…Experimental trails and clinical observations confirmed that inhibition of the mTOR pathway is an attractive therapeutic option, and that it may modify the process of epileptogenesis (Curatolo, 2015;Krueger et al, 2013;Sadowski, Kotulska-Jóźwiak, & Jóźwiak, 2015;Samueli et al, 2016;Stafstrom, Staedtke, & Comi, 2017 (French et al, 2016). The reduction of ≥50% in seizure frequency was significantly higher in patients treated…”
Section: Marijuana Derivativesmentioning
confidence: 86%
“…Experimental trails and clinical observations confirmed that inhibition of the mTOR pathway is an attractive therapeutic option, and that it may modify the process of epileptogenesis (Curatolo, 2015;Krueger et al, 2013;Sadowski, Kotulska-Jóźwiak, & Jóźwiak, 2015;Samueli et al, 2016;Stafstrom, Staedtke, & Comi, 2017). The largest prospective, randomized, multicenter, placebo-controlled study aiming at assessing the effect of Everolimus on seizure frequency in TSC patients with drug-resistant epilepsy (EXIST-3) documented a positive antiepileptic effect of Everolimus as additional antiepileptic therapy with tolerable safety profile (French et al, 2016).…”
Section: Marijuana Derivativesmentioning
confidence: 96%
“…We show that the aberrant sprouting of SOM‐INs is dependent on mTORC1 and that blocking mTORC1 signaling with rapamycin prevents this compensatory phenomenon and aggravates the seizure phenotype. Therefore, although mTOR inhibitors have been advocated as potential antiepileptogenic therapies for patients with genetic epilepsies associated with intrinsic hyperactivation of mTOR (such as in tuberous sclerosis), their use in other circumstances might actually prevent beneficial compensatory mechanisms and aggravate seizures.…”
Section: Discussionmentioning
confidence: 99%
“…Another vascular disorder commonly associated with focal epilepsy is the recognizable Sturge‐Weber syndrome . The condition is characterized by facial hemangiomas, seizures, and in some, varying degrees of intellectual disability . Recently, somatic mutations in GNAQ were identified as a cause of nearly 80% to 90% of Sturge‐Weber cases .…”
Section: Focal Epilepsy Syndromesmentioning
confidence: 99%
“…98 The condition is characterized by facial hemangiomas, seizures, and in some, varying degrees of intellectual disability. 99 Recently, somatic mutations in GNAQ were identified as a cause of nearly 80% to 90% of Sturge-Weber cases. 100,101 Cerebral cavernous malformations (CCMs) are another vascular anomaly that can predispose to focal epilepsy, strokes, and other neurological deficits.…”
Section: Focal Epilepsy Due To Vascular Anomaliesmentioning
confidence: 99%